One Thousand One (1001) Days Out With Your Kids : The Essential Guide to Enjoying Britain's Fun-Packed Family Attractions : From Castles and Museums to Theme Parks and Zoos (Bath BA Parragon Book, 2004)
What it says in the title with all the details of the places to visit opening times, costs location etc.
Include Color Illustrations and Index.
The Essential Guide to Enjoying Britain's Fun-Packed Family Attractions : From Castles and Museums to Theme Parks and Zoos.
Keywords: Great Britain -- Family recreation